CONCEPT OF A DIGITAL SCANNING SYSTEM FOR EQUIPMENT – RICH ROOMS FOR REVERSE ENGINEERING PURPOSES FOR EDUCATIONAL PROJECTS - Strokan, Viktoriia; Neshchadym, Vladyslav (Theory and practice of design, 2023)
The concept of a digital scanning system is housed, saturated with equipment, for the purpose of reverse engineering for educational projects. The purpose of the article is to study the concept of a system of digital scanning of a room saturated with equipment for the purpose of reverse engineering. In this article, we considered the following stages: based on the analysis of foreign and domestic literature, we identified the main factors for solving a number of problems in order to fully achieve the creation of low – budget technologically independent systems for the preparation of digital data for the reverse engineering of complex digital data for the reverse engineering of complex engineering objects by formation of point clouds. In the case of industrial buildings and premises saturated with their equipment and technological communications, it is even higher, and the variety of such filling has a large number of options. A method was chosen for the integration of information into a single digital complex, which bears the sustainable name of BIM – technology. The abbreviation BIM stands for Building Information Model and is actually a universal technological standard that will be widely used when describing the full life cycle of such objects. With today’s pace of scientific and technical development, it is difficult to imagine what the technique and technology of obtaining information about terrestrial objects by photogrammetric methods will be in the near future. The feasibility of using this technology is great in connection with the problem that construction may face, namely, low labor productivity and qualification of the workforce due to large volumes of work, the complexity of control at the construction site, and high material and energy intensity. The possibility of implementing an automated system at the construction site in a short time will reduce the technological components of the construction industry and increase its efficiency. In our work, we will be particularly interested in the tasks of measurement and generation of point clouds, not so much for relatively empty premises (residential rooms, classrooms, public and commercial spaces), as for industrial premises with a high intensity of filling with equipment and communications. This approach is associated with a high intensity of filling with equipment and communications. This approach is connected with the fact that the solution of the problem of forming point clouds for rooms with high occupancy obviously methodically solves the problem for simpler objects. At the same time, almost every building has at least several rooms equipped with supporting engineering systems – pumping, ventilation, electrical, heating points and others. Purpose. To carry out an overview of approaches to reengineering the construction of information models of buildings using the study of geometric parameters of the object with three – dimensional lidar based on digital processing of point clouds. Methodology. It includes the following methods: a complex of generally scientific logical research methods based on the theoretical analysis of technological solutions presented in scientific and technical literature, information resources of developers and mass media, including patents, scientific articles and publications Results. As a result of the research, a technical concept of a low – budget lidar measuring complex based on a two – dimensional lidar was developed. The physical and software architecture has been developed. The result of the stage of the series is described – design, manufacture and verification of a prototype of three – dimensional laser scanning based on a two – dimensional lidar. Scientific novelty. Identified problems and their causes, adjusted research and development program. Practical relevance. The results of the study can be used in digital scanning, which is saturated with equipment for the purpose of reengineering.